On the Possibility That Cyclodextrins' Chiral Cavities Can Be Available on AOT n -Heptane Reverse Micelles. A UV−Visible and Induced Circular Dichroism Study - Silva, Oscar Fernando (2007)
The formation of reverse micelles (RMs) of sodium 1,4-bis(2-ethylhexyl)sulfosuccinate (AOT) in n-heptane including two different â-cyclodextrin (â-CD) derivatives (hydroxypropyl-â-CD, hp-â-CD, and decenyl succinyl-â-CD, Mod-â-CD) is reported. Both cyclodextrins can be incorporated into AOT RMs in different zones within the aggregate, while â-CD cannot. Using UV-vis and induced circular dichroism (ICD) spectroscopy and different achiral molecular probes (some azo dyes, p-nitroaniline and ferrocene), it was possible to determine that Mod-â-CD is located with its cavity at the oil side of the AOT RM interface, while for hp-â-CD the cavity is inside the RM water pool. Among the molecular probes used, methyl orange (MO) was the only one which gave the ICD signal when dissolved in the AOT RMs with hp-â-CD, so a detailed study of MO behavior in homogeneous media was also performed to compare with the microheterogeneous media. The solvatochromic behavior of the dye depends not only on the polarity of the media but also on other specific solvent properties. A Kamlet-Taft analysis shows that the MO absorption spectrum shifts to longer wavelength with an increase in the solvent polarity-polarizability (π*) and the hydrogen donor ability (R) of the medium. MO appears to be almost 3 times more sensitive to the π* parameter than to the R parameter. In addition, from the MO absorption spectral changes with the hp-â-CD concentration, the association equilibrium constants in pure water (K11W) and inside the RMs (K11RM) were computed. The results show that K11W is almost 10 times larger than the value inside the RMs. The latter can be explained considering that MO resides anchored to the RM interface through hydrogen bond interaction with the hydration bound water. This study shows for the first time that the cyclodextrin chiral cavity is available for a guest in an organic medium such as the RMs; therefore, we have created a potentially powerful nanoreactor with two different confined regions in the same aggregate: the polar core of the RMs and the chiral hydrophobic cavity of cyclodextrin.